Stress fractures and bone health in track and field athletes - Nattiv, A. (Journal of Science and Medicine in Sport, 2000)
The effect of exercise on bone health has received much attention in recent years. The problems of the female athlete triad: disordered eating, amenorrhea and osteoporosis have helped us to better understand and appreciate the important interaction of mechanical, hormonal, nutritional as well as genetic factors on bone health in the young female athlete. The relatively high stress fracture incidence of young track and field athletes can be quite disabling for the athlete's present and future running career. A number of risk factors including low bone mineral density (BMD), menstrual irregularities, dietary factors and prior history of stress fractures have been associated with an increased risk for stress fractures in the female athlete. Few studies have found risk factors for stress fractures in the male athlete. Female gender has been found to be a risk factor for stress fractures in the military population, but this finding is less apparent in athlete studies. Caucasians have been found to have a higher risk for stress fractures than African-American military recruits, but there is very limited data assessing stress fracture risk in athletes of varying ethnicity. Prevention of stress injury to bone involves maximizing peak bone mass in the pediatric and young adult age groups. Maintaining adequate calcium nutrition, caloric intake as well as hormonal and energy balance are important preventive measures, as are ensuring appropriate amounts of weight bearing exercise for optimizing bone health and preventing fractures. More research is needed to determine factors leading to improvements in bone density and fracture reduction in athletes at risk.